2015
DOI: 10.1016/j.molcel.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Dependent Effector-like Functions of RIG-I-like Receptors

Abstract: Summary The vertebrate antiviral innate immune system is often considered to consist of two distinct groups of proteins: pattern recognition receptors (PRRs) that detect viral infection and induce the interferon (IFN) signaling, and effectors that directly act against viral replication. Accordingly, previous studies on PRRs, such as RIG-I and MDA5, have primarily focused on their functions in viral double-stranded RNA (dsRNA) detection and consequent antiviral signaling. We here report that both RIG-I and MDA5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 21 publications
3
66
0
Order By: Relevance
“…Of note, the PB2-627E-type viruses are also impaired in cells lacking the signaling adapter MAVS or expressing only a mutant RIG-I (K270A) that is still able to bind RNA but unable to promote antiviral signaling [14 ]. In line with this, it was reported that signalinginactive RIG-I can inhibit hepatitis B virus by binding to the 5 0 -e region of the pregenomic RNA [43 ], and that both RIG-I and MDA5 can actively displace viral proteins from dsRNA [44 ]. Thus, RIG-I has a previously unrecognized RIG-I vs. influenza virus Weber-Gerlach and Weber 73 direct antiviral effect that can precede antiviral signaling [3,45,46].…”
Section: Direct Antiviral Activitymentioning
confidence: 83%
“…Of note, the PB2-627E-type viruses are also impaired in cells lacking the signaling adapter MAVS or expressing only a mutant RIG-I (K270A) that is still able to bind RNA but unable to promote antiviral signaling [14 ]. In line with this, it was reported that signalinginactive RIG-I can inhibit hepatitis B virus by binding to the 5 0 -e region of the pregenomic RNA [43 ], and that both RIG-I and MDA5 can actively displace viral proteins from dsRNA [44 ]. Thus, RIG-I has a previously unrecognized RIG-I vs. influenza virus Weber-Gerlach and Weber 73 direct antiviral effect that can precede antiviral signaling [3,45,46].…”
Section: Direct Antiviral Activitymentioning
confidence: 83%
“…Further investigation of these two SNPs in the context of their effects on transcription factors HNF-3b and AP-1 modulation of IFIH1 expression following IFN-I treatment is warranted. Furthermore, the importance of MDA5 as a direct anti-viral agent further warrants investigation into its expression kinetics in relation to the above two SNPs [64].…”
Section: Resultsmentioning
confidence: 99%
“…The binding of RIG-I to the FLUAV panhandle occurs immediately after the RNPs enter the host cell and can impose a direct antiviral effect via the disassembling of the RdRP complex (13). Also, for other viral systems, it was shown that the binding of RIG-I to regulatory RNA structures can restrict viral functions and result in such a signaling-independent inhibitory activity (14,15). RIG-I activators of FLUAV besides the panhandle structure are erroneous RNA replication products (16) and U/A-rich sequences in the 3= untranslated region (UTR) of the genome segments (17).…”
Section: Influenza a Virus And Rig-imentioning
confidence: 99%